1993
DOI: 10.1002/cne.903360411
|View full text |Cite
|
Sign up to set email alerts
|

Cortical axon trajectories and growth cone morphologies in fetuses of acallosal mouse strains

Abstract: Hereditary absence of the corpus callosum (CC) provides an ideal experiment of nature for exploring mechanisms of axon guidance. In this study the prenatal development of CC axons in the acallosal mouse strains BALB/cWah1 and 129/ReJ or J was compared with normal hybrid mice by using the lipophilic dyes DiI and DiA. A few I/LnJ mice were also examined. The time of emergence and growth rate of CC axons from four cortical regions (frontal, parietal, temporal, occipital) were normal in acallosal strains. Their CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 21 publications
5
54
0
Order By: Relevance
“…However, the precise number and location of the cell bodies of neurons that pioneer the corpus callosum is still under investigation, and markers specific for this subset of neurons are not yet available (37,38,55). Furthermore, in some acallosal strains of mice it has been suggested that the inability to cross the midline may result from deficiencies in the substrates found by axonal growth cones at the midline (56). Thus the aberrant expression of genes in nonneuronal cells that are important for growth cone guidance could generate this acallosal phenotype in the Nfia Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise number and location of the cell bodies of neurons that pioneer the corpus callosum is still under investigation, and markers specific for this subset of neurons are not yet available (37,38,55). Furthermore, in some acallosal strains of mice it has been suggested that the inability to cross the midline may result from deficiencies in the substrates found by axonal growth cones at the midline (56). Thus the aberrant expression of genes in nonneuronal cells that are important for growth cone guidance could generate this acallosal phenotype in the Nfia Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…2 E-I). In addition, a small population of msi1 Ϫ/Ϫ mice (5-10%) exhibited Probst's bundle (8), an entangled axon tract in the corpus callosum (CC), because of errors in the projection of commissural fibers across the midline in the forebrain (Fig. 2 A-D).…”
Section: Results Msi1 ؊/؊ Mice Develop Obstructive Hydrocephalus Withmentioning
confidence: 99%
“…This interpretation is supported by recent data in mice showing that the frontal predominance of the high delta frequencies under increased sleep pressure is reduced as a result of congenital callosal dysgenesis Tobler, 2004a, 2005). In these mice callosal fibres fail to cross the midline and instead form a novel structure -the longitudinal bundle of Probst that provides redundant connectivity predominantly in the rostral portion of the neocortex (Ozaki and Shimada, 1988;Ozaki et al, 1989;Ozaki and Wahlsten, 1993). Moreover, a functional component may contribute to the hyperfrontality.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known for the rat that there are less neurons in the frontal cortex than in the posterior areas (Beaulieu, 1993). On the other hand, frontal areas receive a massive input from the contralateral cortical areas via the corpus callosum (Ozaki and Wahlsten, 1993), from the thalamus (Arbuthnott et al, 1990) and from the brainstem (Lamour et al, 1982;Woolf et al, 1983). Therefore, the relative number of synaptic connections formed in the frontal cortex may be higher compared with other areas.…”
Section: Introductionmentioning
confidence: 99%